QUARTZ FROM HYDROTHERMAL VEINS OF THE ARKAIM AREA, SOUTH URALS: DATA ON VIBRATIONAL SPECTROSCOPY, GAS CHROMATOGRAPHY, AND FLUID INCLUSIONS - M.V. Shtenberg; N.N. Ankusheva (Минералогия, 2015)
Quartz veins from the Arkaim area, South Urals, belong to two volcanogenic-hydrothermal systems: Middle Devonian (gold-sulfide-quartz zones and hematite-quartz edifice) and Early Carboniferous (sulfide-quartz veins in trachybasalts, trachyrhyolites, and microgranosyenite dykes). Volatiles in quartz include H2 O, CO2 , CH4 , and N2 . The H2 O and CO2 contents in the fluid inclusions increase from the lower to upper levels of the systems: from the Eastern to Western gold-sulfidequartz zones and from the bottom to top of the hematite-quartz edifice. In the Early Carboniferous system, the maximum H2 O and CO2 contents are typical of quartz vein from the microgranosyenite dyke. In addition, the CH4 contents in the fluid inclusions decrease upward the section of the volcanic complexes. Hydrotherms were NaCl- and NaCl–KCl-dominant aqueous fluids. Their salinity increases twice upward the section in gold-sulfide-quartz zones, hematite-quartz edifice, and veins in trachybasalts and trachyrhyolites.